Technical Condition Analysis of Main Structures of Yerevan Lake Hydro Facility - Sarukhanyan, Arestak; Hovhannes, Hovhannes; Sahakyan, Aram (Scientific Papers of National University of Architecture and Construction of Armenia, 2023)
The article presents the results of the investigation of the technical condition of the main structures of Yerevan lake hydro facility. It highlights the strength and stability problems of the structures and gives engineering solutions to neutralize them. Lake Yerevan is an important infrastructure that ensures the combined work of transportation, water supply, communication and other engineering facilities of the city of Yerevan. In addition, it is a unique ecological and environmental unit. This extremely important structure must have reliable operating conditions, for which it must be periodically inspected to identify existing structural changes. The technical condition of individual structures of the Yerevan Lake hydro unit was investigated by visual and instrumental methods, and the risks threatening the stability of the structure were identified.